Converging and Diverging Themes: A Synthesis of Contemporary Theological Literature on Disability - Miller, Payton (Journal of disability & religion, 2020)
This paper will engage contemporary theological literature and the prevalent views articulated by contemporary Christian authors regarding disability. The themes will be drawn from the writings of numerous authors and will be disability as God’s purpose, disability and social stigma, disability in relation to intimacy and hospitality, and disability in relation to a biblical ideal. These themes will be analyzed based on their prevalence in Christian thought as well as their positive and negative impact upon Christian praxis most apparent in the Church.